Assessing the Consistency of the Implementation of Duties and Authorities of State Ministries from the Perspective of Administrative Law: A Study of the Food Estate Program and COVID-19 Response during the Second Term of President Joko Widodo’s Administration: Menakar Konsistensi Pelaksanaan Tugas dan Wewenang Kementerian Negara dari Perspektif Hukum Administrasi Negara: Telaah Program Food Estate dan Penanganan Covid-19 pada Periode Kedua Pemerintahan Joko Widodo - Yusuf, Muhammad Rifai; Rohman, Azmi Fathu; Rizqiyanto, Naufal; Hidayat, Syarif (Lex Renaissance, 2025)
The administration of the government has recently shown “bureaucratic irregularities” where the handling of some issues by ministries appointed by the president does not correspond to their main duties. The execution of the food estate program by the Ministry of Defense and the handling of the Covid-19 by the Ministry of State-Owned Enterprises are clear case samples. To find out which ministry truly has the authority, this research seeks to examine the consistency of the authorities of the two ministries with the affairs handled through the cultivation of two main problems. First, what is the position, duties and authority of state ministries both in the regulatory framework and the existing theory/doctrine explanations in administrative law. Second, to what extent is the consistency of the implementation of the duties and authorities of the ministries that become the focus of the study from the perspective of administrative law. This research is normative legal research by describing and analyzing qualitatively secondary data i.e. primary and secondary legal materials. The approach method used are conceptual and statutory approaches. The results showed that the position and authorities of state ministries in Indonesia have clear legal bases including the ministries that have authority in food estate and Covid-19 handling, namely the Ministry of Agriculture and the Ministry of Health. Thus, the Ministry of Defense which is the leading sector in the food estate program and the Ministry of State-Owned Enterprises in handling Covid-19 show bureaucratic inconsistencies.